Mediterranean Sea large-scale low-frequency ocean variability and water mass formation rates from 1987 to 2007: A retrospective analysis. (March 2015) - Pinardi, Nadia; Zavatarelli, Marco; Adani, Mario; Coppini, Giovanni; Fratianni, Claudia; Oddo, Paolo; Simoncelli, Simona; Tonani, Marina; Lyubartsev, Vladislav; Dobricic, Srdjan; Bonaduce, Antonio
Abstract: We describe a synthesis of the Mediterranean Sea circulation structure and dynamics from a 23-year-long reanalysis of the ocean circulation carried out by Adani et al. (2011). This mesoscale permitting dynamical reconstruction of past ocean variability in the Mediterranean Sea allows the study of the time-mean circulation and its low frequency, decadal, components. It is found that the time-mean circulation is composed of boundary and open ocean intensified jets at the border of cyclonic and anticyclonic gyres. The large scale basin circulation is generally characterized in the northern regions by cyclonic gyres and in its southern parts by anticyclonic gyres and eddy-dominated flow fields, with the exception of the Tyrrhenian and the northern Ionian Sea. The time-mean Tyrrhenian Sea circulation is dominated by cyclonic gyres of different intensity and intermittency. The northern Ionian Sea circulation, however, reverses in sign in two ten-year periods, the first in 1987–1996 and the second in 1997–2006, which is here called the Northern Ionian reversal phenomenon. This reversal is provoked by the excursion of the Atlantic-Ionian Stream from the middle to the northern parts of the basin. The decadal variability of other parts of the basin is characterized by changes in strength of the basin scale structures. The water mass formation rates and variability are dominated by event-like periods where the intermediate and deep waters are formed for 2–3 years at higher rates. The largest deep water formation events of the past 23 years occurred separately in the western and eastern Mediterranean basin: the first coincided with the Eastern Mediterranean Transient (Roether et al., 1996) and the second with the western Mediterranean deep water formation event in 2005–2006 (Smith et al., 2008). A new schematic of the basin-scale circulation is formulated and commented.